(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study investigated the growth performance and carcass characteristics of the African giant snail (Archachatina marginata) fed varying inclusions levels of Aspilia africana and Moringa oleifera leaf meals. A total of forty-eight snails were used for this experiment which was carried out for eight weeks at the Faculty of Agriculture, Department of Animal Science Teaching and Research Farm, Nnamdi Azikiwe University, Ifite-ogwari. Feeding trial comprises four treatment groups: one control (0% mixed leaf meals) and three experimental groups with 5%, 10%, and 15% inclusions of mixed leaf meal. A completely randomized design (CRD) was used, and each treatment was replicated three times with four snails per replicate. One-way ANOVA was used to analyze the result and significantly different means were separated using Duncan Multiple Range Test. Results indicated that snails on the 10% inclusion diet (T3) demonstrated significantly (P<0.05) higher total weight gain and average daily weight gain (18.67 g, 0.33 g/day) respectively compared to other treatments. Other growth parameters measured were not significantly different. Result showed that all parameters measured on carcass characteristics were not significantly different across the treatments. In conclusion, study showed that mixed leaf meal can be incorporated into snail diets without adverse effects. It was therefore recommended that 10% mixed leaf meal (T3) be included in the diets of African giant snails for better total weight gain and average daily weight gain.